1988
DOI: 10.1042/bj2520001
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1:2(cyclic),4,5-trisphosphate is not a major product of inositol phospholipid metabolism in vasopressin-stimulated WRK1 cells

Abstract: 1. A method has been devised for quenching cell incubations with an aqueous phenol/chloroform/EDTA mixture of neutral pH, to allow the analysis of acid-labile cell components. 2. Using this method, we have searched for the appearance of Ins(1:2cyclic,4,5)P3 [inositol 1:2(cyclic),4,5-trisphosphate] in WRK1 mammary tumour cells that were labelled to high specific radioactivity with [3H]inositol and then stimulated with 0.4 microM-vasopressin. 3. Vasopressin caused a very rapid accumulation of Ins(1,4,5)P3 (inosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Insufficient material was available from the unstimulated and 5 s samples for their enantiomeric configurations to be determined. The small amounts of iditol and glucitol found in the oxidation products do, however, suggest the presence in peak 11 of small amounts of Ins(1,2-cyclic,4,5)P3, as previously reported in these cells by Wong et al (1988): opening of the cyclic phosphate ring, presumably during periodate treatment, would give rise to Ins(1,4,5)P3 and Ins(2,4,5)P3, which would yield these two hexitols after oxidation.…”
Section: Inositol Bisphosphatesmentioning
confidence: 59%
See 4 more Smart Citations
“…Insufficient material was available from the unstimulated and 5 s samples for their enantiomeric configurations to be determined. The small amounts of iditol and glucitol found in the oxidation products do, however, suggest the presence in peak 11 of small amounts of Ins(1,2-cyclic,4,5)P3, as previously reported in these cells by Wong et al (1988): opening of the cyclic phosphate ring, presumably during periodate treatment, would give rise to Ins(1,4,5)P3 and Ins(2,4,5)P3, which would yield these two hexitols after oxidation.…”
Section: Inositol Bisphosphatesmentioning
confidence: 59%
“…Peak 2: Ins(1,2cyc1ic)P. The early elution of peaks 1 and 2 suggested that one of them might be Ins(1:2cyclic)P, whose presence was expected, since Ins(I:2cyclic,4,5)P3 (Wong et al, 1988) and Ins(l :2cyclic,4)PJ (see below) have been seen in these cells. These peaks were isolated from control cells and those stimulated for 5 s, 30 s and 10 min, by extraction with the neutral phenol/chloroform medium: they were then acid-treated to open any acid-labile five-membered cyclic phosphate ring.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations